LEGAL CULTURE OF FARMERS AS A GUARANTEE FOR THE DEVELOPMENT OF FARMING ENTERPRISES - Daminov Khusniddin Absalomovich (PT. Antis International Publisher, 2024)
Objective: This study explores the significance of legal awareness in enhancing the success of farming enterprises in Uzbekistan. It aims to identify the challenges farmers face regarding legal support and education, and proposes solutions for improving legal knowledge within the agricultural sector. Method: A qualitative research approach is employed, utilizing legal analysis, case studies, interviews with farmers, legal experts, and policymakers, along with data from government publications and surveys. This methodology helps to understand the current legal challenges and gaps in farmers' legal education. Results: The study reveals several challenges, including the lack of legal support due to limited financial resources, uninformed contract signing, limited access to legal information, and inadequate accounting practices. These factors lead to legal disputes, financial losses, and hindered growth for farmers. Novelty: The novelty of this study lies in its focus on legal culture as a tool for empowering farmers. It emphasizes the importance of continuous legal education, access to professional legal services, and the integration of technology to address these challenges. By promoting legal awareness and improving legal access, the study provides a roadmap for the growth and sustainability of farming enterprises in Uzbekistan.